Horizontal band-saw - Foot, R. M.; Boardman, G. E. T.; Dailey, B. R.; Baller, E. G. A.; Noble, C. F. (College of Aeronautics, 1964)
The effect of various parameters on the performance of the band saw when cutting mild steel-with a 10 t.p.i. raker-set blade were established over a limited range. These are discussed fully in the ‘conclusions'. With this limited survey it was not found possible to establish the optimum conditions of operation.